Post-embryonic Development of the Circadian Clock Seems to Correlate With Social Life Style in Bees - Beer, Katharina; Helfrich-Förster, Charlotte (Frontiers in Cell and Developmental Biology, 2020)
Social life style can influence many aspects of an animal’s daily life, but it has not yet been clarified, whether development of the circadian clock in social and solitary living bees differs. In a comparative study, with the social honey bee, Apis mellifera, and the solitary mason bee, Osima bicornis, we now found indications for a differentially timed clock development in social and solitary bees. Newly emerged solitary bees showed rhythmic locomotion right away and the number of neurons in the brain that produce the clock component Pigment-Dispersing Factor (PDF) did not change during aging of the adult solitary bee. Honey bees on the other hand, showed no circadian locomotion directly after emergence and the neuronal clock network continued to grow after emergence. Social bees appear to emerge at an early developmental stage at which the circadian clock is still immature, but bees are already able to fulfil in-hive tasks.